Longitudinal Lipid Trajectories and Progression of CKD in Children - Uwe Querfeld; Marietta Kirchner; Francesca Mencarelli; Karolis Azukaitis; Aysun Bayazit; Ali Duzova; Anke Doyon; Nur Canpolat; Ipek Kaplan Bulut; Lukasz Obrycki; Justine Bacchetta; Rukshana Shroff; et al. (Kidney International Reports)
Introduction: There are discrepant findings regarding the effect of dyslipidemia on disease progression in adult patients with chronic kidney disease (CKD). Methods: In a prospective cohort study of children with stage 3 to 5 (predialysis) CKD, triglycerides (TGs), total cholesterol (CHOL), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were measured semiannually. We investigated whether CKD progression is associated with serum lipid levels at baseline and with lipid trajectories during follow-up. CKD progression was defined as the time to a composite event of 50% reduction in estimated glomerular filtration rate (eGFR), eGFR < 10 ml/min per 1.73 m2, or start of kidney replacement therapy. By semiparametric group-based trajectory modeling (GBTM), 2 trajectories were defined for each lipid, termed “high” and “low.” Results: A total of 681 patients aged 12.2 ± 3.3 years with a mean eGFR of 26.9 ± 11.6 ml/min per 1.73 m2 were included. Kidney diagnosis was classified as congenital anomalies of the kidneys and urinary tracts (CAKUT) in 69%, glomerulopathy in 8.4%, and other disorders in 22.6% of patients. During a median of 5.1 years of follow-up, 59% of patients reached the composite end point. Kidney survival was significantly different for HDL-C (P = 0.0128), but not for other lipid trajectories in the Kaplan-Meier analysis. There was no significant association of any of the lipid trajectories with CKD progression in Cox proportional hazard models. Variables consistently associated with CKD progression in models for each lipid at baseline and for lipid trajectories included age, a diagnosis other than CAKUT, eGFR at baseline, albuminuria, the serum albumin level, and diastolic blood pressure (BP). Conclusions: These data do not support an important role for lipids in the progression of CKD in children.